Ensuring the Rule of Law under Martial Law: A Comparative Study of Constitutional Mechanisms - Kelbia, Stella; Lutskyi, Roman; Skomorovskyi, Vitalii; Polishchuk, Olexandr; Lysak, Maksym; Скоморовський, Віталій Богданович; Поліщук, Олександр Сергійович; Лисак, Максим Юрійович; Скоморовський, Віталій (Universita degli Studi di Milano, 2025)
The study explores the rule of law under martial law in various states (including the United States, the United Kingdom, France, Israel, and Ukraine) and highlights the need for a balance between national security and protection of human rights. The study found that restrictive measures, such as curfews, restrictions on freedom of movement and assembly, censorship and military courts, were common in many countries during martial law. However, the extent and duration of these restrictions vary greatly. An effective rule of law requires clear legal regulation, an independent judiciary, effective governance mechanisms, and transparency of state bodies. Successful cases demonstrate the importance of international cooperation and exchange of experience in strengthening the rule of law during military conflicts. © 2025, Universita degli Studi di Milano. All rights reserved.